Creating a postmortem examination decision aid: Suggestions from bereaved parents of a stillborn. (July 2023) - Riches, Naomi O.; Workalemahu, Tsegaselassie; Johnson, Erin P.; Silver, Robert M.; Lopez, Sarah; Page, Jessica; Sartori, Brittney; Rothwell, Erin
Abstract: Objectives: To understand the postmortem decision-making needs and preferences of parents of a stillborn. Methods: A qualitative content analysis was conducted. Patients who received stillbirth care at the University of Utah in the last 5 years, were 18 years of age or older, and English speakers, were invited to participate via an email and follow-up phone call. Participants were interviewed about their experiences, values, beliefs, decision-making experience regarding the postmortem examinations of their stillborn, and suggestions for how to assist their decision-making needs. Results: Nineteen participants who consented to one or more postmortem examination of their stillborn were interviewed. They expressed needing information, altruism, and/or a belief in science as reasons for consenting. The most common reason for declining was already knowing the stillbirth cause. Recommendations for a decision aid included a description of all stillbirth evaluation options, risks and benefits, and a timeline. Conclusion: Participants had a variety of reasons for consenting to or declining postmortem examinations of their stillborn. Recommendations for a decision aid include a full description of each examination, the risks and benefits, and a timeline. Practical implications: An example decision aid was created from recommendations, which presents balanced information to help support couple's decision-making. Highlights: Postmortem examinations can provide information about the cause of a stillbirth. Decision making to undergo these examinations is complex with long-lasting impacts. Decision aids can help patients make informed decisions according to their values. Patient suggestions for a decision aid and an example are presented.